Soft skills related to strategic management and the management system of quality laboratories (Gestión y Gerencia, 2024)
The study is limited around beverage manufacturing companies, specifically those that have within their structure: production area and quality departments or management, responsible for monitoring the characteristics of the process, that is, units dedicated to control quality of raw materials, the manufacturing process and the manufactured products. The actions of those in charge of these managements require the development of particular skills, since it is an area of the organization related to testing laboratories where they quantify the various quality parameters, whether physicochemical, microbiological and/or sensory. Therefore, the purpose of the research is to analyze the profile of soft skills associated with the strategic management of quality laboratories, which operate with a management system based on the ISO/IEC 17025:2017 standard. To this end, aspects related to the topic were evaluated, along with the case study of eight (8) quality laboratory coordinators: three (3) belonging to alcoholic fermentation beverage production companies and five (5) in soft drink and non-carbonated beverage manufacturing plants. Among the most relevant evidence is that laboratory management requires the development of a series of soft skills such as effective communication, leadership, flexibility, resilience, among others, that allow it to comply with the set of activities, with the complexity that entails this system of management, as well as, with the meshing of the management strategies and the ethical essentials of the company.
Keywords: soft skills; management; ISO 17025; management system